Modelo de Cox para análise da sobrevida das empresas de plano de saúde no Brasil. - de Oliveira, Silvando Carmo; de Almeida, Renan Moritz Varnier Rodrigues (JBES: Brazilian Journal of Health Economics / Jornal Brasileiro de Economia da Saúde, 2019)
Objective: In Brazil, studies on the survival time of health insurance providers are scarce. Thus, this article aims to investigate economic factors that explain the survival of these companies. Methods: The statistical technique survival analysis was used (Cox semi-parametric model). Data were obtained from the ANS (regulatory agency) website and refer to 929 operators from all regions of the country, 2011-2018. The following variables were analyzed: Beneficiaries (average number of beneficiaries per provider), Size (Size 1: Up to 20 thousand beneficiaries, Size 2: Between 20 thousand and 100 thousand beneficiaries, Size 3: Above 100 thousand beneficiaries) Time in market (Number of quarters that the provider remained in the market), Revenue/Expenses (Very Low, Low, High and Very High), Profit (Providers that profited and providers that did not profit), Type of Management (Nonprofit Management and For profit/Business Management) and lastly the (dependent) Bankruptcy variable, which indicates if the operator requested the ending of its activities. Results: A higher mortality rate was observed for small providers compared to the others, with a probability of non-survival in the market two times smaller in relation to medium-sized companies and three times lower than the large ones. Conclusions: Small businesses are at a great disadvantage in the Brazilian panorama of health insurance providers, regardless of their life time in the market.